2015
DOI: 10.1021/am508119c
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Capacitance of Ni-Doped Metal Organic Framework and Reduced Graphene Oxide Composites: More than the Sum of Its Parts

Abstract: Composites of a Ni-doped metal organic framework (MOF) with reduced graphene oxide (rGO) are synthesized in bulk (gram scale) quantities. The composites are composed of rGO sheets, which avoid restacking from the physical presence of MOF crystals. At larger concentration of rGO, the MOF crystals are distributed on the overlapping and continuous rGO sheets. Ni in Ni-doped MOF is found to engage in a two-electron, reversible, efficient, redox reaction shuttling between Ni and Ni(OH)2 in aqueous potassium hydroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(105 citation statements)
references
References 52 publications
4
100
0
1
Order By: Relevance
“…For example, Yang et al synthesized Zn-doped Ni-MOF as an active material for SCs. [87] In comparison with ah igh charge-transferr esistance of 184 mW for pure MOF-5,t he Ni-doped MOF-5 exhibits much lower resistanceo fo nly 74 mW.W ith reducedc harge-transferr esistance, the Ni-dopedM OF-5 provides ad ramatically increased capacitance of 240 Fg À1 at ac urrent density of 50 mA g À1 , whereas the capacitance of pure MOF-5 is only 100 Fg À1 . Another example, Co 8 -MOF-5e lectrode with Zn cations partially substituted by Co cations, has been reported for enhanced performance of SCs.…”
Section: Pristinemofs For Scsmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Yang et al synthesized Zn-doped Ni-MOF as an active material for SCs. [87] In comparison with ah igh charge-transferr esistance of 184 mW for pure MOF-5,t he Ni-doped MOF-5 exhibits much lower resistanceo fo nly 74 mW.W ith reducedc harge-transferr esistance, the Ni-dopedM OF-5 provides ad ramatically increased capacitance of 240 Fg À1 at ac urrent density of 50 mA g À1 , whereas the capacitance of pure MOF-5 is only 100 Fg À1 . Another example, Co 8 -MOF-5e lectrode with Zn cations partially substituted by Co cations, has been reported for enhanced performance of SCs.…”
Section: Pristinemofs For Scsmentioning
confidence: 96%
“…[86] The mixed-metal-based MOF structure shows much better SC performance than that of most single metal oxide based electrodes, owing to improvede lectric conductivity.R ecently,B anerjee et al demonstrated the enhanced electric conductivity of Ni-doped MOF-5 by using electrochemical impedance spectroscopy (EIS). [87] In comparison with ah igh charge-transferr esistance of 184 mW for pure MOF-5,t he Ni-doped MOF-5 exhibits much lower resistanceo fo nly 74 mW.W ith reducedc harge-transferr esistance, the Ni-dopedM OF-5 provides ad ramatically increased capacitance of 240 Fg À1 at ac urrent density of 50 mA g À1 , whereas the capacitance of pure MOF-5 is only 100 Fg À1 .…”
Section: Pristinemofs For Scsmentioning
confidence: 96%
“…It seems reasonable to assign the bands to vibrations in the organic part H 2 BDC of MIL‐125(Ti) . More precisely, these peaks correlate to the asymmetric and symmetric stretching vibrations of the carboxylate as well as the vibrations of CC and CH bonds from the benzene ring . For rGO/MIL‐125(Ti) and Ag/rGO/MIL‐125(Ti), no obvious peak shifts of the MOF bands are observed except for the appearance of bands associated with rGO.…”
Section: Resultsmentioning
confidence: 97%
“…Banerjee et al [114] synthesized MOF-5 NiRGO in bulk (gram scale) quantities. The composites were prepared by mixing Ni-doped MOF-5 with RGO (Fig.…”
Section: Carbon-based Materials As Additional Materialsmentioning
confidence: 99%